Independent Agencies dalam Struktur Ketatanegaraan Republik Indonesia - Syukron Jazuly (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
This research studies theoretical construction of independent agencies in constitutional structure of Republic of Indonesia, and aims at researching and positioning its theoretical construction, characteristics, and also the forms of its checks and balances towards the original three branches.This normative legal research combines perspectives of conceptual approach, as well as statutory, comparative, and historical ones, in which the implementation conducted accordingly by need.By using the various theories created by some classical and contemporary theorists in term of independent agencies, and limitation of powers themes, as it has been implemented in constitutional law practice and revised in theoretical perspective, the result of this study shows independent agencies are a different branch of government, compare to the conception of Montesquieu’s trias politica. Indonesian constitutional lawpractice attracts fact about an existence of a different branch of government, where it is referred to as the independent agencies. As a new type of separation of power, theoretical construction of independent agencies could be referred to as "The New Separation of Power."The result of this study also shows independent agencies existance in constitutional structure of Republic of Indonesia is still be placed under primary state agencies, and considered as auxiliary state agencies.